Affiliative Strategies to Manage Rapport in Spanish and British Medical Consultations - Hernández López, María De La O (Estudios Ingleses de la Universidad Complutense, 2009)
The present study is framed within the Rapport Management (Spencer-Oatey, 2000, 2008) and Sociopragmatic Interactional Principles theories (Spencer-Oatey and Jiang, 2003) to examine the strategies developed in medical consultations in Spain and England which enhance doctor-patient relationships. One of the strategies that appeared in the data analysed showed that there are affiliative strategies to display closeness with the listener, although the type of strategy and the way to deal with closeness-distance greatly varies between these two socio-cultural settings. It is so because there are different communicative styles based on Sociopragmatic Interactional Principles rooted in every culture depending on specific considerations of face, rights and obligations and interactional goals in the mind of interlocutors. There may be various motivations to find this: the existing power asymmetry between interlocutors together with different cultural assumptions about the rights and obligations they assume in medical consultations will consequently imply a different way of managing relations, and therefore affiliative strategies may be constrained by this worldview.The present study will then explore the existing interconnection between the culturally biased concepts of power and rights and obligations, on the one hand, and pragmatic affiliative strategies, on the other, as a result of those conceptualizations.